If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17x + 6 = 106 Reorder the terms: 6 + 17x = 106 Solving 6 + 17x = 106 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 17x = 106 + -6 Combine like terms: 6 + -6 = 0 0 + 17x = 106 + -6 17x = 106 + -6 Combine like terms: 106 + -6 = 100 17x = 100 Divide each side by '17'. x = 5.882352941 Simplifying x = 5.882352941
| 16-3m=7-6(m+2) | | 10x-25=105 | | 80+x=171 | | 34+4x=-5(x+4) | | -3x-3(1+1)=-15 | | 55x=605 | | 2x+-2=10-4 | | 4y+9=17-2y | | 43+x=410 | | x-24=64 | | -3X^2+90=0 | | 5x=430 | | 4x-5y-9x+8y=0 | | 2x^2-lnx+1=0 | | 90-x^2=0 | | -x+3+12x=-4+4x+42 | | 5x-15x^3=5x(1-3x^2) | | (x+8)+4=x+(4+8) | | 3w^2-10w+8=0 | | -4(2+3n)=-56 | | 2(a+3)=5a-1 | | -4-4(2+4v)=-44 | | a-4(2a+4)=-44 | | 10a=45 | | 3(2+4x)=-42 | | 5(y^2-14y+49)=-90 | | 5x-12a=7-2x | | 2.4(m-3)+3.8=-32 | | 3x(x)+8x=9 | | 10n^2-9n=9 | | 6(y+x+2+x+4)=18 | | 3(x+1)+2(x+2)=2x+10 |